Oxford studies in ancient philosophy - Inwood, Brad (Oxford studies in ancient philosophy., 2012)
$a Oxford Studies in Ancient Philosophy is a volume of original articles on all aspects of ancient philosophy. The articles may be of substantial length, and include critical notices of major books. OSAP is now published twice yearly, in both hardback and paperback.'The serial Oxford Studies in Ancient Philosophy (OSAP) is fairly regarded as the leading venue for publication in ancient philosophy. It is where one looks to find the state-of-the-art. That the serial, which presents itself more as an anthology than as a journal, has traditionally allowed space for lengthier studies, has tended only to add to its prestige; it is as if OSAP thus declares that, since it allows as much space as the merits of the subject require, it can be more entirely devoted to the best and most serious scholarship.'Michael Pakaluk, Bryn Mawr Classical Review